2020
DOI: 10.1021/acs.jpcb.0c06265
|View full text |Cite
|
Sign up to set email alerts
|

Complex Roles of PsbS and Xanthophylls in the Regulation of Nonphotochemical Quenching in Arabidopsis thaliana under Fluctuating Light

Abstract: Protection of photosystem II against damage from excess light by nonphotochemical quenching (NPQ) includes responses on a wide range of timescales. The onset of the various phases of NPQ overlap in time making it difficult to discern if they influence each other or involve different photophysical mechanisms. To unravel the complex relationship of the known actors in NPQ, we perform fluorescence lifetime snapshot measurements throughout multiple cycles of alternating 2 min periods of high light and darkness. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 81 publications
(187 reference statements)
2
30
0
Order By: Relevance
“…Figure 1B presents light intensity profiles of NPQ determined for A. thaliana WT as well as for the npq1 and npq4 mutants. As can be seen, the simultaneous presence of both Zea and PsbS protein is necessary for the photosynthetic apparatus to develop a significantly high photoprotective response, in accordance with the previous reports (Niyogi et al, 1998;Li et al, 2000;Steen et al, 2020). The levels of NPQ determined for different genotypes of A. thaliana in the present work are in agreement with the reported values corresponding to comparable light intensities (Kress and Jahns, 2017).…”
Section: Chlorophyll Fluorescence Quenching In Leavessupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 1B presents light intensity profiles of NPQ determined for A. thaliana WT as well as for the npq1 and npq4 mutants. As can be seen, the simultaneous presence of both Zea and PsbS protein is necessary for the photosynthetic apparatus to develop a significantly high photoprotective response, in accordance with the previous reports (Niyogi et al, 1998;Li et al, 2000;Steen et al, 2020). The levels of NPQ determined for different genotypes of A. thaliana in the present work are in agreement with the reported values corresponding to comparable light intensities (Kress and Jahns, 2017).…”
Section: Chlorophyll Fluorescence Quenching In Leavessupporting
confidence: 93%
“…It has been demonstrated that the most effective excitation quenching requires the simultaneous presence of both the PsbS protein (Li et al, 2000) and zeaxanthin (Zea) (Niyogi et al, 1998), a xanthophyll accumulated under high light conditions in consequence of de-epoxidation of violaxanthin (Vio) within the xanthophyll cycle (Jahns et al, 2009) (see Supplemental Figure 1). Moreover, overexpression of PsbS in plants results in enhanced light-induced excitation quenching (Steen et al, 2020). The significant quenching of Chl a excitations has been observed in reconstituted LHCII with the presence of Zea and PsbS, although neither PsbS nor Zea alone was sufficient to induce the same effect (Wilk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The initial step of photosynthesis involves the absorption of light. However, when the amount of light absorbed exceeds the capacity of its photosynthetic utilization, this can lead to the formation of reactive oxygen species (ROS) and damage to the photosynthetic apparatus [ 1 , 2 ]. To reduce the risk of potential damage plants evolved protective mechanisms, including ways to minimize light absorption, detoxify ROS and dissipate excess light energy as heat [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Method used is adapted for fluorescence lifetime snapshot from (59) and transient absorption spectroscopy snapshot from (60). For fluorescence lifetime measurements, time-correlated single photon counting (TCSPC) was performed on detached leaves, isolated thylakoids and gel filtration fractions.…”
Section: Fluorescence Lifetime and Transient Absorption Spectroscopy Snapshotmentioning
confidence: 99%